Child as Method as a Resource to Interrogate Crises, Antagonisms and Agencies - Burman, Erica (Estudos e Pesquisas em Psicologia, 2022)
In this article, I discuss the peculiar ‘agencies’ attributed to the child/childhood under neoliberalism as a symptom of its crises and antagonisms, with a focus also on practical struggles and solidarities such analyses might promote/afford. Specifically, the theme of this Special Issue aligns with an approach I have named ‘Child as method’, which analyses the geopolitical dynamics and intersections performed and resisted by practices around children and childhood. I will start by outlining key starting points for the discussion that follows, such as the relation between the child and (neo)liberalism, and the child as a site of consumption/display. I outline the ways the child, as a cypher for the modern late capitalist European subject, has been aligned with imperialism, colonialism and extractive racial capitalism as a particular reading of Freud’s ‘His Majesty the Baby’. Following this, I explore a range of subject (including affective) positions accorded children (which children themselves may sometimes occupy), as an expression of Child as Method’s commitments to map how ‘child’ reflects and contributes to transnational geopolitical dynamics, in the service of identifying new subjective possibilities and relations.